Peningkatan Keterampilan Menyimpulkan Melalui Model Pembelajaran Inkuiri Terbimbing (Guided Inquiry) Pada Mata Pelajaran IPA Kelas V Sekolah Dasar - Arumingtyas, Pramesti; Kartono, Kartono; Riyadi, Riyadi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
The purpose of this research is to improve the concluding skill through model guided inquiry. This form of research is a classroom action research conducted three cycles. Each cycle consists of four stages of planning, action, observation, and reflection.Â  Data collection techniques are using tests, observations, interviews and documentation. Data validity tests are using triangulation. Data analysis technique used is the interactive model. The results showed the average value of preaction class score of 42,91 with 10,81% classical completeness increased to 53,91 with 18,92% classical completeness in cycle I and increased again to 68,41 with 51,35% classical completeness in cycle II, then in cycle III increased again to 82,43 with 81,08% classcal completeness. Based on the result of the research, it can be concluded that through the application of model guided inquiry can improve the concluding skill for V grade students of SD N Karangasem II Surakarta in the academic year 2017/2018